1985
DOI: 10.1002/jmv.1890150205
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in upper and lower Egypt

Abstract: The relative prevalence of hepatitis B surface antigen (HBsAg), anti-HBs, and anti-hepatitis B virus core antigen (HBc), as markers of hepatitis B virus infection, among 1,866 apparently healthy residents of two Egyptian provinces representing Upper and Lower Egypt populations was determined using solid-phase radioimmunoassay (SPRIA). The prevalence rate of HBsAg in the Egyptian population was moderately high (10.1%); it was higher in the Upper Egypt (11.7%) than the Lower Egypt (8.0%) population and more freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 3 publications
0
17
0
2
Order By: Relevance
“…Similar to other African countries [Greenfield et al, 1986;Windsor et al, 1984;Said et al, 1985;Gebreselassie, 1984;Coursaget et al, 1984;Ahmed et al, 1984;Werner et al, 1985;Sebastiani et al, 1985;Sherif, 1985;Khalfa and Ardjoun, 1984;Henriksen, 1984;Bowry, 1983;Prozesky et al, 1983;Gebreselassie, 1983a;Bowry, 19831 prevalence of hepatitis B markers is high among Ethiopians: by the age of 20 over 70% of the healthy young men are already positive to at least one marker, indicating that most of the infections occur at an earlier age. This feature of a common infection occurring early in life explains the high rate of liver cirrhosis and primary liver carcinoma observed in Ethiopia [Health Manpower Study: "Ethiopia"; The Ministry of Health, Addis Ababa Ethiopia, 1980; Lester and Tsega, 19761.…”
Section: Discussionmentioning
confidence: 79%
“…Similar to other African countries [Greenfield et al, 1986;Windsor et al, 1984;Said et al, 1985;Gebreselassie, 1984;Coursaget et al, 1984;Ahmed et al, 1984;Werner et al, 1985;Sebastiani et al, 1985;Sherif, 1985;Khalfa and Ardjoun, 1984;Henriksen, 1984;Bowry, 1983;Prozesky et al, 1983;Gebreselassie, 1983a;Bowry, 19831 prevalence of hepatitis B markers is high among Ethiopians: by the age of 20 over 70% of the healthy young men are already positive to at least one marker, indicating that most of the infections occur at an earlier age. This feature of a common infection occurring early in life explains the high rate of liver cirrhosis and primary liver carcinoma observed in Ethiopia [Health Manpower Study: "Ethiopia"; The Ministry of Health, Addis Ababa Ethiopia, 1980; Lester and Tsega, 19761.…”
Section: Discussionmentioning
confidence: 79%
“…However, low-intermediate (2-4 %) prevalence of HBV has been reported in North Africa and Middle Eastern region across all age groups in 2005 [11••]. In a study published in 1985, prevalence of HBsAg among residents of two Egyptian provinces was as high as 10.1 % with anti-HBc found in 88 % [37]. More recent data suggests intermediate endemicity levels [38,39], and even low (<2 %) prevalence has been reported among blood donors [40,41].…”
Section: Eastern Mediterraneanmentioning
confidence: 95%
“…Previous studies reported that the seroprevalence of anti-HBs antibodies among the Egyptian adult population due to past asymptomatic infection ranges from 30% to 60%. [24][25][26][27][28] Literature contains very limited data on the safety of long-acting progestin-only methods among women with serological markers of past hepatitis BV infection. Among our women it was found that those with clinical and biochemical evidence of cure from clinical viral hepatitis B and C were still having some residual abnormalities in liver cells that adversely interacted with Norplant.…”
Section: Discussionmentioning
confidence: 99%